Exploring Formation Mechanism of Medical Collaborative Practices in Multi-level Market from an Infra-marginal Perspective - Wang, Sufen; Zhao, Shuqi; Xu, Mengqi; Xia, Hanqian; Yuan, Junyi (Journal of Global Economy, Business and Finance, 2025)
This study aims to formally analyze the emergence and evolution of medical collaborative practices (MCPs) in multi-level market. From an infra-marginal perspective, it constructs a role generation model of collaborators, and extracts eight role models and six structures with corner equilibrium. Finally, three structures (structure A with no market, structure CN with single-level market and structure CC with two-level market) have global equilibrium. With the increase of learning cost of medical services and medical transaction services, two evolution paths of MCPs "A - >CN -> CC" and "CN -> CC ->A" are more likely to appear.